Suriani Nasi Kukus a New Experience. - Siti Rohana Idris (NewStraits Times, 2018)
Kota Bahru: In addition to serving a delicious menu with a variety of side dishes, the Suriani Nasi Kukus restaurant here has been gaering towards customers comfort and with uniqueness.